AG-Based Thick-Film Front Metallization of Silicon Solar Cells - M. Prudenziati; L. Moro; B. Morten; F. Sirotti; L. Sardi (Active and Passive Electronic Components)
The evolution of microstructure and electrical properties of silver-based thick-film metallizations of silicon solar cells prepared by infrared firing processes has been investigated. The performance of the cells are shown to be dependent on several dynamical and diffusive phenomena. In particular, the sintering of silver grains, silver diffusion into the glass, and the flow of glass at the metal/silicon interface strongly affect important characteristics of the cells such as sheet and contact resistivities and the adhesion of fingers and bus bars. The existance of an optimum value of the peak firing temperature is observed and explained in terms of competitive phenomena occurring at the metal/silicon interface. Moreover it is shown that IR firing treatments require a careful consideration of the sequence of printing and firing steps. The features of heat treatments performed in conveyor belt furnances using Joule and infrared sources are compared.